Serum Pregenomic RNA Combined With Hepatitis B Core-Related Antigen Helps Predict the Risk of Virological Relapse After Discontinuation of Nucleos(t)ide Analogs in Patients With Chronic Hepatitis B - Wang, Fa-Da; Zhou, Jing; Li, Lan-Qing; Wang, Meng-Lan; Tao, Ya-Cao; Wang, Yong-Hong; Zhang, Dong-Mei; Chen, En-Qiang (Frontiers in Microbiology, 2022)
Background and aim: Cessation of nucleos(t)ide analogues (NAs) therapy in patients with chronic hepatitis B(CHB) is uncommon. Although criteria for discontinuation appear in some guidelines, the indicators for assessing discontinuation of NAs are limited, whether NAs can be safely ceased remains a difficult clinical issue. Our study aimed to investigate the role of serum pregenomic RNA (pgRNA) and hepatitis B core-associated antigen (HBcrAg) at the end of treatment (EOT) in guiding the safe discontinuation of NAs in CHB patients. Methods: This is a retrospective study, clinical data of all CHB patients who discontinued NAs treatment at West China Hospital between June 2020 and January 2021 were collected, including EOT pgRNA, HBcrAg, HBsAg, etc. All patients should meet the Asian-Pacific guideline for discontinuation. Observing virological relapse (VR) rates during 1 year of NAs discontinuation and analyzing the relationship between EOT pgRNA, HBcrAg and VR. Results: A total of 64 patients were enrolled in this study and 33(51.5%) patients experienced VR in one year. EOT pgRNA positivity (OR=14.59, p=0.026) and EOT higher HBcrAg levels (OR=14.14, p=0.001) were independent risk factors for VR. The area under the receiver-operating characteristic (AUROC) value of EOT HBcrAg for VR was 0.817 (p<0.001), optimal cut-off value was 3.3 log10 U/ml. Patients with EOT pgRNA positivity and EOT HBcrAg ＞3.3 log10 U/ml were more likely to experience VR after discontinuation of NAs (88.9% vs 45.5% p=0.027). Conclusion: According to current guidelines, a higher VR rate occurs after cessation of NAs. EOT pgRNA positivity and higher HBcrAg level carries a higher risk of VR. Combining these novel markers can better help us assess whether patients can safely cease NAs treatment.